Strut and Tie Modelling of Reinforced Concrete Deep Beams Under Static and Fixed Pulsating Loading - Quadri, Ajibola Ibrahim (Al-Nahrain Journal for Engineering Sciences, 2020)
Numerical analysis of the performance of reinforced concrete (RC) deep beam subjected to static and fixed-point pulsating loading at the midpoint has been investigated. Three-dimensional nonlinear finite element model using the Strut and Tie approach was adopted. The damage level under the influence of the applied fixed pulsating loading is higher than the static applied loading, hence early crack was observed because of the stepwise loading in the form of vibration. Although the Strut and Tie approach gave a good estimation of the resistance capacity of the beam, the beam undergo high shear damage when subjected to these two types of loading. Material strength properties, applied loadings and cross-sections adopted are some of the factors that affect the performance of the deep beam.